The U.S.-China Nuclear Agreement: A Failure of Executive Policymaking and Congressional Oversight - Homer, Daniel; Leventhal, Paul (Tufts Archival Research Center, 2005)
Volume 11, Issue 1. Winter The agreement for nuclear cooperation signed by the United States and China in July 1985 is a watershed for U.S. policy on preventing the spread of nuclear weapons. It provides an important barometer of the current commitment in Washington to the requirements of U.S. nonproliferation law and sets a precedent for future U.S. nuclear agreements. The results, conclude Daniel Homer and Paul Leventhal, are not encouraging. In negotiating the agreement, the Executive Branch allowed China to avoid key requirements of U.S. law. Congress had ample opportunity to remedy these defects but chose simply to paper them over. Mr. Homer and Mr. Leventhal describe and comment upon the process by which the U.S.-China agreement was negotiated and reviewed and consider the implications of this flawed agreement.